Sapindaceae Juss. em remanescente de floresta estacional semidecidual no sul do Brasil : um estudo da Estação Ecológica do Caiuá, PR. - Rosado, Aline (2013)
The total amount of species in the world is between 10 and 30 million, but the majority of them still waits for scientific discoveries, especially in tropical regions. This high biodiversity is endangered, mainly by human actions and among the areas that have been drastically depleted, the riparian ones are of particular concern, once they are related to the balance of the aquatic ecosystem, which is essential to the survival of many species. These areas are located in the vicinity of water bodies and its vegetation is dependent, at some degree, on the hydrological regime. Thus, the growing need for floristic surveys in these formations is justified, since it is from them that we can get the knowledge about the structure, the functioning and the dynamics of the riparian ecosystem, generating subsidies for protection and recovery actions. Therefore, the aim was to conduct a floristic survey of the family Sapindaceae in Caiuá Ecological Station, located on the left bank of Paranapanema river, and develop identification keys, morphological descriptions and photographic illustrations to subfamilies, tribes, genera and species; also, we aimed at gathering information about species distribution and periods of flowering and fruiting. The study area, with about 1449.48 ha, is located in the phytogeographical domain Atlantic Forest and at the Stational Semideciduous Forest phytophysiognomy, between the coordinates 22º29'S and 52º51'W, in the county Diamante do Norte, Paraná State, Brazil. Partial floristic surveys conducted in this Protected Area listed 71 families, 188 genera and 322 species, of which eight genera and 10 species were listed for Sapindaceae. The study material was obtained from self-made collections and the collections from the Herbaria of the State University of Maringá (HUEM) and the State University of Londrina (FUEL). Twenty species were recognized, grouped in nine genera, four tribes and one subfamily, Sapindoideae Burnett. One genus and 10 species are new records for the study area. Among the tribes, Paullinieae Kunth had the highest species richness, with four genera and 13 species and among the genera, Serjania Mill. was the richest one, with eight species. Rare species, according to the distribution in the area, were Cupania vernalis Cambess., Matayba elaeagnoides Radlk., Paullinia elegans Cambess., P. spicata Benth., Sapindus saponaria L. Serjania tripleuria Ferrucci and Thinouia mucronata Radlk. All species and genera are native of Brazil, and Cupania tenuivalvis Radlk. is also endemic. S. tripleuria Ferrucci is a new citation for the state of Paraná and the Southern of Brazil. All species were observed in dry areas and in areas prone to flooding, and Paullinia elegans and P. spicata occurred exclusively in wetlands or areas subject to flooding. Eleven species were found exclusively on the edges of forest fragments. Nine species occurred both in the edge and in the interior of the area, so no one occurred exclusively in the interior.